PEMBENTUKAN LIFE SKILL MELALUI PEMBELAJARAN PKN - Suprihatin, Titin; Munandar, M Aris; Setiajid, Setiajid (Unnes Civic Education Journal, 2015)
Education Ministry data reveals that in 2007 only 17.25% of high school students who can continue to pursue higher education either S1 or diploma This means there are 82.75%, or equivalent high school-age children are not able to pursue a higher education. Data from BPS reveals that the majority of open unemployment is high school graduate or equivalent (15.2%). The magnitude of the unemployment rate of high school graduates is one factor they are unprepared to enter the workforce. Therefore, it is necessary to learning that leads to the formation of student life skill. The results showed that SMAN Pati has implemented life skill based learning and the students has applied those skills in in everyday life.